1985
DOI: 10.1111/j.1744-7348.1985.tb03107.x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of leaf growth in sugar beet.

Abstract: SUMMARY The influence of season, and certain agronomic treatments (irrigation, nitrogen fertiliser, density of planting and sowing date) on leaf number were analysed in a series of sugar‐beet crops grown during the five seasons 1978‐82. Leaf appearance was a linear function of thermal time (accumulated temperature above 1°C) and could be described by four variables: a) the thermal duration of the seedling establishment phase, d′s; b) the thermal time interval between appearance of each of the early leaves, θe;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 22 publications
2
36
0
Order By: Relevance
“…At harvest, the prevalence of S1 in terms of active canopy and the simultaneous restraint of the lost canopy (dead leaves weight and number) may be seen as a mechanism of plant resilience in response to early water stress, somewhat enabling it to slow leaf turnover (Milford et al , 1985). This may be proved by the fact that S1, although it is the treatment that has produced the lowest total foliar biomass (dead plus green leaves) during plant life, has kept 55% of its activity up to harvest.…”
Section: Discussionmentioning
confidence: 99%
“…At harvest, the prevalence of S1 in terms of active canopy and the simultaneous restraint of the lost canopy (dead leaves weight and number) may be seen as a mechanism of plant resilience in response to early water stress, somewhat enabling it to slow leaf turnover (Milford et al , 1985). This may be proved by the fact that S1, although it is the treatment that has produced the lowest total foliar biomass (dead plus green leaves) during plant life, has kept 55% of its activity up to harvest.…”
Section: Discussionmentioning
confidence: 99%
“…Plant leaf number (all leaves more than 2 mm long, including dead ones) was used as the measure of growth stage. The number of day-degrees above 1°C between the appearance of successive sugarbeet leaves remains constant as the plant grows (Milford et al, 1985b) so plant leaf number also serves as a measure of plant age in thermal-time. Leaf area was estimated using length x maximum breadthx 0.75 (Milford et al, 1985a).…”
Section: Methodsmentioning
confidence: 99%
“…Thermal-time intervals for leaf emergence and expansion (Milford et al, 1985a(Milford et al, , 1985b were used to estimate which leaves were expanding and which were fully-grown when the aphids were counted. Aphids occurred at higher density on leaf categories found to be suitable in the clip-cage experiments; that is young, expanding leaves and those showing strong virus symptoms ( fig.…”
Section: Experiments 4 Aphid Distribution and Population Development mentioning
confidence: 99%
“…Studies on the effects of N on leaf area per plant (Gastal et al, * FAX No: +5415211384 1992; Gastal and Nelson, 1994;Vos and Biemond, 1992) have shown that it is reduced under N stress mainly by reduction in the area of individual leaves, although reductions in leaf number may occur under extreme conditions (Connor et al, 1993;Steer and Hocking, 1983). In dicots the effects of N supply on the final area of a leaf is linked to its effects on the rate of leaf expansion (LER) rather than the duration of the expansion and the magnitude of the effects are modulated by leaf position on the stem (Milford et al, 1985;Vos and Biemond, 1992). In grasses, LER is also very responsive to N application Muchow, 1988).…”
Section: Introductionmentioning
confidence: 99%